Solution of Fuzzy Non-linear Equation using Bisection Algorithm - Saha, Goutam Kumar; Shirin, Shapla (Dhaka University Journal of Science, 2013)
In Classical Mathematics a non-linear equation can be solved by using different types of numerical methods. In this paper a new approach has been introduced to get approximate solutions of a fuzzy non-linear equation with the help of Bisection Algorithm. A non-linear equation over linear fuzzy real numbers is called a fuzzy non-linear equation. Finally, graphical representations of the solutions has also been drawn so that anyone can achieve the idea of converging to the root of a fuzzy non-linear equation. Dhaka Univ. J. Sci. 61(1): 53-58, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15096